2001
DOI: 10.1007/bf02234460
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four hour recordings of colonic motility in patients with diverticular disease

Abstract: We concluded that patients with diverticular disease of the colon have abnormal motor and propulsive activities of the large bowel, which are confined to the affected segments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 28 publications
2
77
1
10
Order By: Relevance
“…Paradoxically, inflating a balloon in the colon of individuals with DD induces the musculature of the colonic wall to yield to the increasing luminal pressure more quickly than in controls [38,39] . In addition, these and later studies indicate increased colonic motility (as assessed by number and amplitude of bowel wall contractions) in the sigmoid colon of individuals with left-sided DD [40,41] , and also in the ascending colon of patients with right-sided diverticulosis [42] . These classical studies were generally performed with low numbers and failed to account for age, gender, physical activity or body fat percentage; the physiological observations were made under artificial conditions, i.e.…”
Section: Intra-luminal Pressure and Colonic Motilitymentioning
confidence: 79%
See 1 more Smart Citation
“…Paradoxically, inflating a balloon in the colon of individuals with DD induces the musculature of the colonic wall to yield to the increasing luminal pressure more quickly than in controls [38,39] . In addition, these and later studies indicate increased colonic motility (as assessed by number and amplitude of bowel wall contractions) in the sigmoid colon of individuals with left-sided DD [40,41] , and also in the ascending colon of patients with right-sided diverticulosis [42] . These classical studies were generally performed with low numbers and failed to account for age, gender, physical activity or body fat percentage; the physiological observations were made under artificial conditions, i.e.…”
Section: Intra-luminal Pressure and Colonic Motilitymentioning
confidence: 79%
“…Furthermore, they were performed over one or two hours, with the subject at rest, whilst in reality one would expect variation in bowel pressures throughout the day. More recently however, Bassotti et al [41] made recordings over a 24 h period, and observed higher colonic motility in DD cases throughout the recording period than in a younger control group (cases 42-65 mmHg, controls 37-55 mmHg). It is unclear whether or not failing to control for age confounds these studies; Firth and Prather [43] suggest that colonic motility is not altered in the normal ageing colon, but this warrants further investigation, ideally utilizing pressure-sensitive transducers which can be swallowed and allowed to pass through the GI tract to provide more representative measures of colonic physiology [44] .…”
Section: Intra-luminal Pressure and Colonic Motilitymentioning
confidence: 97%
“…Twenty-four-hour colonic motor activity in both patients and controls was studied by a previously described manometric technique [23, 24, 25, 26]. After an overnight fast, an eight-lumen manometric probe with side holes spaced 12 cm apart (Arndorfer Medical Specialties, Greendale, Wisc., USA; outer diameter 4.5 mm, inner diameter for each lumen 0.8 mm) was introduced within the colon by the aid of a colonoscope.…”
Section: Patientsmentioning
confidence: 99%
“…More recently, we investigated colonic motility in patients with symptomatic uncomplicated diverticular disease, by means of a 24-hour manometric technique that allows studying most of the viscus, its daily fluctuations [57] , and detection of the motor equivalents of mass movements, the so-called high-amplitude propagated contractions (HAPC) [58] . With respect to controls, patients with diverticulosis displayed a significantly overall increase of daily motor activity, except in the transverse colon (the segment not involved by diverticula), and of propulsive activity [59] . Interestingly, patients had several retropropagated HAPC (never observed in controls), and the motor activity of the affected segments, especially the sigmoid, was significantly higher than that of the unaffected ones (the transverse).…”
Section: Colonic Motilitymentioning
confidence: 86%